Preparation and In-Vitro Evaluation of Ketoconazole-Loaded Niosome (Ketosome) for Drug Delivery to Cutaneous Candidiasis - Katayoun Morteza-Semnani; Majid Saeedi; Jafar Akbari; Maryam Moazeni; Amirhossein Babaei; Reza Negarandeh; Maedeh Azizi; Mohammad Eghbali; Seyyed Mohammad Hassan Hashemi (Tabriz University of Medical Sciences, 2023)
Background: Recently, niosomes are becoming popular in drug delivery. The current work aimed to investigate the characteristics, cellular safety, and antifungal activity of ketoconazole-loaded niosome (ketosome). Methods: Ultrasonic approach was employed to prepare ketosome including cholesterol, nonionic surfactant and ketoconazole. The size characteristics and morphological features of ketosome and physicochemical properties of ketoconazole in ketosomes were evaluated using dynamic light scattering (DLS), differential scanning calorimetry (DSC), powder x-ray diffractometer (PXRD), scanning electron microscopy (SEM), and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy. Also, the dissolution rate, cellular safety test and antimycotic properties of ketosome were examined. Results: According to the results, the particle size of the ketosome decreased from 491.400±10.622 to 121.300±7.274 nm by the increment of cholesterol. According to further research, changes in the cholesterol:surfactants ratio can modulate the zeta potential from -27.866±1.069 to -12.500±1.153 mV. The highest entrapment of ketoconazole was about 87% when the cholesterol concentration in the ketosome was high. Ketosome with the maximum cholesterol:surfactants ratio showed the fastest drug release. Furthermore, the cell viability assay revealed that the ketosome had lower cytotoxicity in comparison with pure drug. The cell viability of the ketosome was estimated to be about 90% (HGF cell line). The ketosome had a lower MIC than the pure drug when tested against Candida albicans. Conclusion: The results of this study revealed that the optimized ketoconazole-loaded niosome could be used as a possible nanovesicle for ketoconazole drug delivery, potentially opening up new ways for the management of cutaneous candidiasis complaints.